Iron catalyzed demethylation of acetic acid - Comba, Peter; Faltermeier, Dieter; Keppler, Frank; Schöler, Heinz Friedrich; Schroll, Moritz (Journal of coordination chemistry, 2018)
The iron(IV)-oxo catalyzed cleavage of acetic acid is reported. Iron(II) complexes are used as catalyst precursors and H2O2 as oxidant in reactions in aqueous solution with an excess of chloride and, in some experiments, with ascorbic acid added as an OH. radical scavenger. It is shown that the acetic acid is cleaved into CO2 and a methyl radical. In the presence of O2 and OH. radicals, the initially generated methyl radicals produce methanol and formate. Halogenated alkanes are also formed and, in the absence of O2 and OH. radicals, methane is obtained as the major product. A mechanism for the formation of various environmentally important volatile C1 compounds is deduced from the present results and published studies, and its relevance as an additional source for these compounds in the atmosphere is discussed.